Three step flow focusing enables image-based discrimination and sorting of late stage 1 Haematococcus pluvialis cells - Kraus, Daniel; Kleiber, Andreas; Ehrhardt, Enrico; Leifheit, Matthias; Horbert, Peter; Urban, Matthias; Gleichmann, Nils; Mayer, Guenter; Popp, Juergen; Henkel, Thomas (PLoS ONE, 2021)
Label-free and gentle separation of cell stages with desired target properties from mixed stage populations are a major research task in modern biotechnological cultivation process and optimization of micro algae. The reported microfluidic sorter system (MSS) allows the subsequent investigation of separated subpopulations. The implementation of a viability preserving MSS is shown for separation of late stage 1 Haematococcus pluvialis (HP) cells form a mixed stage population. The MSS combines a three-step flow focusing unit for aligning the cells in single file transportation mode at the center of the microfluidic channel with a pure hydrodynamic sorter structure for cell sorting. Lateral displacement of the cells into one of the two outlet channels is generated by piezo-actuated pump chambers. In-line decision making for sorting is based on a user-definable set of image features and properties. The reported MSS significantly increased the purity of target cells in the sorted population (94%) in comparison to the initial mixed stage population (19%).
CRIS-Team Scopus Importer:2023-04-20